Every patient tells a story : medical mysteries and the art of diagnosis - Sanders, Lisa, 1956- (Broadway Books, 2009)
Presents an unflinching look inside the detective story that marks nearly every illness-the diagnosis-revealing the combination of uncertainty and intrigue that doctors face when confronting patients who are sick or dying--from the challenges of the physical exam to the pitfalls of doctor-to-doctor communication, the vagaries of tests, and the near calamity of diagnostic errors.